Neutrophil‐mediated vascular barrier injury: Role of neutrophil extracellular traps. (April 2017) - Meegan, Jamie E.; Yang, Xiaoyuan; Coleman, Danielle C.; Jannaway, Melanie; Yuan, Sarah Y.
Abstract: Neutrophils play an essential role in host defense against infection or injury. While neutrophil activation is necessary for pathogen clearance and tissue repair, a hyperactive response can lead to tissue damage and microcirculatory disorders, a process involving complex neutrophil–endothelium cross talk. This review highlights recent research findings about neutrophil‐mediated signaling and structural changes, including those induced by neutrophil extracellular traps, which ultimately lead to vascular barrier injury.